NCAPD3 is involved in papillary thyroid carcinoma proliferation, metastasis, and aerobic glycolytic pathway - Liubing Zhang; Aiping Peng; Yue Qin (Discover Oncology)
Abstract Objective To examine the expression of non-SMC condensin II complex subunit D3 (NCAPD3) in papillary thyroid carcinoma (PTC) tissues, assess its impact on the growth and metastatic potential of PTC cells, and investigate its role in regulating glycolysis to uncover the underlying mechanisms involved. Methods NCAPD3 levels in PTC tissues were detected using immunohistochemistry. siRNA transfection was used to silence NCAPD3 in K1 and TPC-1 cells. Cell proliferation rates were detected using the Cell Counting Kit-8 assay, migration rates were evaluated using wound healing and Transwell cell migration assays, and invasion rates were assessed using the Transwell-Matrigel cell invasion assay. Moreover, the aerobic glycolysis-related factors lactate, lactate dehydrogenase A (LDHA), and pyruvate kinase M2 (PKM2) were detected using kits. Results NCAPD3 was highly expressed in PTC tissues. Its expression showed no significant association with patient age, gender, or lymphocytic thyroiditis but was significantly correlated with larger tumor size and lymphovascular invasion. NCAPD3 expression significantly decreased in K1 and TPC-1 cells after transfection with siRNA. Low NCAPD3 expression reduced the proliferation rate of K1 and TPC-1 cells and inhibited cell migration and invasion. Moreover, NCAPD3 silencing decreased LDHA, PKM2, and lactate levels. Conclusions NCAPD3 was highly expressed in PTC tissues, and correlated with aggressive features (tumor size and lymphovascular invasion). NCAPD3 silencing inhibited proliferation, migration, invasion, and aerobic glycolysis of PTC cells. Therefore, NCAPD3 may serve as a potential therapeutic target for PTC.